ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI DIVIDEND PAYOUT RATIO PADA PERUSAHAAN MANUFAKTUR YANG LISTED DI BEI TAHUN 2008 – 2012 - Gama Primadasa, Dwi; Muharam, Harjum (Diponegoro Journal of Management, 2015)
This research aims to determine the impact of Return On Equity, Debt to Equity Ratio, Current Ratio, Firm Size, and Growth on Dividend Payout Ratio on manufacturing companies listed in Indonesia Stock Exchange since period 2008 - 2012. This study used secondary data with entire population of manufacturing companies listed in the Indonesia Stock Exchange (BEI) in 2008 - 2012. The method used to determine the sample using purposive sampling and the data obtained on the basis of publication financial report from www.idx.co.id. The analytical method used is multiple linear regression, regression testing prior to first tested the classical assumptions.Based on the statistical F indicates that the model is fit because has significance value less than 5% of alpha value (α). Meanwhile, based on statistical t test showed that the Return on Equity is positive and significant impact on Dividend Payout Ratio. On the other side, Debt to Equity Ratio, Current Ratio and Firm  Size are positive but has no  significant impact due to over Alpha value.  And the last one, Growth has negative and significant impact on Dividend Payout Ratio.Results of the analysis show that predictive ability to the five independent variables (ROE, DER,  CR,  Firm Size,  Growth)  is  19.9% and  it  shown  by  adjusted  R²  value,  the  rest  80.1% influenced by other variables outside the model.